Body mass index: short‐ and long‐term impact on kidney transplantation. Issue 11 (12th August 2015) - Orlic, L.; Mikolasevic, I.; Jakopcic, I.; Grskovic, A.; Jelic Pranjic, I.; Racki, S.; Stimac, D.
Summary: Aim: The topic of pretransplantation body mass index (BMI) is still a matter of controversy. The aim of this study was to investigate the influence of pretransplant BMI on short‐ and long‐term outcomes in patients receiving kidney transplant. Methods: We have analysed 521 renal transplant recipients (RTRs). BMI was categorised as follows: less than or equal to 20, more than 20 to less than or equal to 25, more than 25 to less than or equal to 30 and more than 30 Results: The distribution of the RTRs per category of BMI at baseline was: ≤ 20 (14.4%), > 20 to ≤ 25 (50.9%), > 25 ≤ 30 (26.9%) and > 30 (7.9%). In further analysis, the patients were stratified into four groups according to their pretransplant BMI values. There was no difference in the rates of delayed graft function between the four analysed groups of patients. Recipients with normal pre‐transplant BMI were less likely to develop wound complications in comparison to the recipients with high BMI (p = 0.04) and obese recipients (p = 0.0001). RTRs with normal BMI were less likely to develop lymphoceles in comparison to the recipients with high BMI (p = 0.0003). Obese patients were more likely to develop lymphocele in comparison to the recipients with high BMI (p = 0.01). Obese recipients had a longer mean length of hospital stay in comparison to the recipients with normal BMI (p = 0.04). There was no significant difference regarding 1‐year graft and patient survival, as well as because of acute rejection crisis between the investigated groups of recipients. We did not find any significant difference in 5‐year patients and graft survival between those RTRs with BMI > 20 to ≤ 25 and to those recipients with BMI > 25. Conclusion: Overweight and obese transplant candidates should not be excluded from kidney transplantation.